Dermatologic Manifestations In Chronic Kidney Disease Patients On Hemodialysis - P Shrestha; M Mathur (Nepal Journal of Dermatology, Venereology & Leprology, 2016)
Introduction: Dermatologic changes are frequently seen in chronic kidney disease (CKD) patients. Early identification of these manifestations helps timely institution of treatment and prevention of progression of CKD.